2017
DOI: 10.1177/1742395316675023
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to participate in advance care planning: A qualitative study of renal failure patients, families and healthcare providers

Abstract: Objectives Advance care planning is the process by which people reflect upon their wishes and values for healthcare, discuss their choices with family and friends and document their wishes. Readiness represents a key predictor of advance care planning participation; however, the evidence for addressing readiness is scarce within the renal failure context. Our objectives were to assess readiness for advance care planning and barriers and facilitators to advance care planning uptake in a renal context. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 29 publications
3
50
0
Order By: Relevance
“… 236 288 289 Family members felt ACP was necessary as a means to protect patients. 290–292 At the end of life, maintaining control was a struggle with respect to autonomy and dignity. 134 136 205 251 Patients based their dialysis withdrawal or non-acceptance decision on having lived a full life, on nature taking its course, on their fear of being a burden for their families, their bodies being invaded and dialysis accelerating death.…”
Section: Resultsmentioning
confidence: 99%
“… 236 288 289 Family members felt ACP was necessary as a means to protect patients. 290–292 At the end of life, maintaining control was a struggle with respect to autonomy and dignity. 134 136 205 251 Patients based their dialysis withdrawal or non-acceptance decision on having lived a full life, on nature taking its course, on their fear of being a burden for their families, their bodies being invaded and dialysis accelerating death.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the sensitive nature of these topics, both healthcare providers and cancer patients consider readiness for ACP an important factor when deciding whether or not to engage in an ACP conversation. Some studies have defined readiness as being prepared for action [17] or being willing to engage in a discussion about one's values and wishes with one's family and HCP [16,18,19]. Studies of ACP based on these definitions often consider readiness as a prerequisite for a conversation.…”
Section: Introductionmentioning
confidence: 99%
“…9 The barriers and facilitating actions that nonprofits identified in our study as 'most important' were also found to be important in studies focusing on the perspectives of the public. 12,[17][18][19][20][21][22] As we developed the options in the survey from the literature, it makes sense that our findings supported the existing literature. A 2019 survey of the Canadian public, with provincial breakdowns, resulted in similar 'top' barriers and facilitating actions for British Columbia;…”
Section: Discussionmentioning
confidence: 74%
“…The question about barriers to ACP included a list of 15 items representing the most frequently mentioned barriers in recent Canadian literature from a patient/ caregiver perspective. 10,[16][17][18][19][20][21][22][23][24] For details about this literature search, please see Appendix SA. We restricted our search to Canadian literature to maximize its applicability to our population.…”
Section: Survey Designmentioning
confidence: 99%